Edukasi Makanan Halal dan Thoyyib pada Wali Murid Sekolah Shibghoh Akhlak Qur’an Kota Bekasi - Pujilestari, Shanti; Sabariman, Mohammad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Halal is permitted and thoyyib means good. The issue of halal food and thoyyib is interesting because Indonesia is a country with a majority Muslim population. In the Qur'an, Allah SWT has regulated the obligation to consume halal and thoyyib food, namely in Surah Al Baqarah verse 168. However, understanding and attitudes about halal food and thoyyib in daily life are still lacking, even though the partner is the mother's father/guardian. students from the Shibghoh Akhlak Qur'an school in Bekasi City, which is a community group in a good Islamic religious environment. Low understanding and attitudes will cause behavior towards halal food and thoyyib to also be low. The aim of this activity is to increase understanding and attitudes towards halal and thoyyib food among partners. The methods used are education and discussion. The results of the pretest and post-test showed that there was an increase in the understanding and attitude of the parents of Shibghoh Akhlak Qur'an school students towards halal food. Understanding of halal food increased by 62.7% with an attitude of 59%. Meanwhile, attitude of thoyyib food has been good since before education, so there is no increase in attitude of thoyyib food. There was an increase in thoyyib food attitudes of only 1%. Participants gave positive responses to the activities that had been carried out.